Dynamics of motion of a pair of particles in a supersonic flow - Utkin, P. S.; Sidorenko, D. A.; Boiko, V. M. (Shock waves, 2021)
The problem of motion dynamics of two particles in a supersonic flow behind an incident shock wave was considered numerically and experimentally. The experiments were carried out in a shock tube. High-speed shadowgraphy with a laser stroboscope light source was used. The mathematical model was based on the two-dimensional Euler equations. The original, highly scalable, parallel algorithm of the Cartesian grid method for simulation of flows with shock waves in areas with changing geometry was used in the numerical simulations. The main stages of the process were described from the point of view of the realized shock-wave configurations. The effect of changing two modes of supersonic flow around two particles was obtained. The experimental and simulated flow patterns and dynamics of particle motion correlate well.